Local Fault Line Tracing in Sri Mulyo Village, Dampit Sub District, Malang Regency Based on Geophysical Data - Wasis Wasis; Sunaryo Sunaryo; Adi Susilo (Natural B, Journal of Health and Environmental Sciences, 2011)
A research has been conducted for searching local fault at Sri Mulyo Village, Malang Regency, to get the physical parameters of 3-dimension fault, which include depth, width, length, and direction. The research is based on the preliminary research that results geological data interpretation, gravity, and outcrops.  The survey used resistivity parameter by applying pseudo-depth section configuration (4 electrodes). Data processing and interpretation using inverse method.  By combining every pseudo depth section, 3-dimension physical parameters will be acquired square error is 2.51x10-27.